Ex-ante economic impact of the biotechnological research on cassava brown streak disease in eastern and southern Africa - Manyong, Victor M.; Vercauteren, K.; Tollens, E.F. (International Association of Hydrological Sciences, 2012)
Cassava brown streak disease (CBSD) is a major threat to cassava production in eastern and southern Africa. While the conventional breeding approach is being used to address the problem, biotechnology can also be an option. This paper presents results from an ex-ante assessment of returns to biotechnological research to control CBSD in three countries of eastern and southern Africa (Malawi, Mozambique, and Tanzania) worse affected by the virus. Returns to research can yield benefits as high as US$ 260 million at 10% discount rate over a projected period of 25 years. Mozambique share of the benefits was the biggest because of its largest share in the cassava producing area. Among the parameters used in the surplus economic model for data analysis, the maximum adoption rate has most influence on the results. The other main challenge consists in collecting accurate data to run such analyses. Despite these challenges, biotechnology should be considered as an option in the control of CBSD or other biotic stresses on agricultural commodities in Africa.